Prevalence and Management of Complications of Ureteroscopy: A Seven-Year Experience With Introduction of a New Maneuver to Prevent Ureteral Avulsion - Taie, Karim; Jasemi, Majid; Khazaeli, Dinyar; Fatholahi, Ali (Urology Journal, 2012)
Purpose: To evaluate the prevalence and type of rigid ureteroscopy complications and suggest a new method for ureteral avulsion prevention. Materials and Methods: Between March 2002 and March 2009, we retrospectively evaluated 2955 patients who had undergone diagnostic or therapeutic ureteroscopy for asymptomatic hematuria, migrated ureteral stent, or transurethral lithotripsy. They were enrolled from four hospitals in Ahvaz, Iran. Results: Complications were encountered in 241 (8%) patients, including transient hematuria (4.2%), mucosal erosion (1.4%), stone migration (1.3%), ureteral perforation (1.2%), and fever and/or sepsis (1.0%). Ureteral avulsion occurred in 6 (0.2%) patients. Mostly, complications were managed conservatively, using ureteral stenting. Ureteral avulsions were managed using a new technique. Conclusion: In our series, the complication rate is comparable with the literature. A new technique was used in case of ureteroscope entrapment in the ureter, to lessen the occurrence of ureteral avulsion.